2018
DOI: 10.1002/adem.201701171
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ductility of a Fine‐Grained Mg–Gd–Al–Zn Magnesium Alloy by Hot Extrusion

Abstract: The grain refinement by dynamic recrystallization (DRX), the enhancement of room-temperature strength and ductility by decreasing hot extrusion temperature, and the effect of grain growth at elevated temperatures are discussed for a newly developed as-cast Mg-Gd-Al-Zn magnesium alloy. The results are supported by fracture surface observations, texture analysis by Schulz reflection method based on X-ray diffraction (XRD), and work-hardening rate plots. It is found that by decreasing the extrusion temperature, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The relationship between tensile strength and elongation of various steel grades [3] and the results of the present study are shown, where the non-dual phase steels considered in the present work follow the conventional trend observed in the literature with tensile toughness (TS 3 El [30,31]) values of 20 000 MPa·% or lower, Figure 5. This is also the case for the dual phase steels originated from the spheroidized and full annealed initial microstructures (DP1, DP2, DP5, and DP6), Figure 5.…”
Section: Summary Of Tensile Propertiessupporting
confidence: 78%
“…The relationship between tensile strength and elongation of various steel grades [3] and the results of the present study are shown, where the non-dual phase steels considered in the present work follow the conventional trend observed in the literature with tensile toughness (TS 3 El [30,31]) values of 20 000 MPa·% or lower, Figure 5. This is also the case for the dual phase steels originated from the spheroidized and full annealed initial microstructures (DP1, DP2, DP5, and DP6), Figure 5.…”
Section: Summary Of Tensile Propertiessupporting
confidence: 78%
“…This results in the tardiness of the microcavity coalescence, which leads to deeper dimples. Deep dimples are indicative of high ductility of the material . Upon investigating the fracture surfaces of Fe‐31Ni‐0.1C alloy, Chawla et al found that the density of dimples increases by decreasing grain size, which is consistent with fracture surfaces of Figure for the AISI 304 stainless steel.…”
Section: Resultsmentioning
confidence: 72%
“…Tensile testing was carried out at room temperature by a computerized testing machine at the constant cross‐head speed of 1 mm min −1 to obtain engineering stress ( S )–engineering strain ( e ) curves. The values of work‐hardening rate were determined based on dσ/dε|i={σi+1σi1}/{εi+1εi1}, where σ=S(1+e) and ε=ln(1+e) are true stress and true strain (logarithmic strain), respectively. The instantaneous (incremental) work‐hardening exponent ( n ) based on the Hollomon equation (σ=kεn or lnσ=lnk+nlnε) was also considered.…”
Section: Methodsmentioning
confidence: 99%
“…With increasing Al content from 1 to 4 wt%, the maximum intensity of basal texture of as‐extruded Mg – Al samples decreased from 8.91 to 5.29, which indicated that Al content could weaken the basal texture in magnesium alloys. She and Pourbahari also reported that the intensity of basal texture would decrease with increasing Al content. Decreasing grain size resulted in multi‐peak characteristics with greater orientation distribution of basal poles and then decreased the maximum basal texture intensity of as‐extruded Mg – Al alloy significantly.…”
Section: Resultsmentioning
confidence: 88%